Understanding the foundations of the structural similarities between marketed drugs and endogenous human metabolites - O'Hagan, Steve; Kell, Douglas B. (Frontiers in Pharmacology, 2015)
Background. A recent comparison showed the extensive similarities between the structural properties of metabolites in the reconstructed human metabolic network (‘endogenites’) and those of successful, marketed drugs (‘drugs’). Results. Clustering indicated the related but differential population of chemical space by endogenites and drugs. Differences between the drug-endogenite similarities resulting from various encodings and judged by Tanimoto similarity could be related simply to the fraction of the bitstrings set to 1. By extracting drug/endogenite substructures, we develop a novel family of fingerprints, the Drug Endogenite Substructure (DES) encodings, based on the ranked frequency of the various substructures. These provide a natural assessment of drug-endogenite likeness, and may be used as descriptors with which to derive quantitative structure-activity relationships (QSARs). Conclusions. ‘Drug-endogenite likeness’ seems to have utility, and leads to a simple, novel and interpretable substructure-based molecular encoding for cheminformatics.